Por uma imagem da literatura: a poética do escancaramento do diretor Luiz Fernando Carvalho - Guzzi, Cristiane Passafaro [UNESP] (2015)
The possibility of a detailed study of the creative process of TV miniseries based on the transposition of literary works, instigated us to want to understand in a more rigorous way the relationship between literature and cinema, literature and television, in the work done by director Luiz Fernando Carvalho. The enunciation of his television accomplishments Hoje é dia de Maria (2005); A Pedra do Reino (2007); Capitu (2008) produces discourses that gather the story of the work in question and the history of the criticism of the short stories and novels transposed in a deliberate and updated way. Carvalho, when read as a critical enunciator in his syncretic productions, consolidates an unveiling poetics between the verbal text and the syncretic text, and that can be understood as the specific composition procedures that show up in a reiterated way in his accomplishments, establishing a TV metafiction. Our hypothesis, therefore, for the consolidation of this poetics is that Carvalho's base element of differentiation consists in the fact that he bases himself on the recurrence with which the denouncement of his compositions procedures is made, creating a recurring sense of estrangement in the viewer, once we find the echo of the first work, the verbal one, associated with the translation done for a new support, lined, by a game between the tradition searched and its own reinvention in a wide open way. This way, he is able to produce other meanings for the work, not only due to the exploration of metalinguistic procedures along the plot but specially because he reveals unveiling resources, allowing his miniseries to be read inside a highly reflexive fictionality that mimics its own concept of fiction. Within a practice of exaggeration and unveiling of the making process that characterizes his TV accomplishments, we find subtleties that open a path for a profound study of the transposed literary work, of the criticism, the tradition and...